Problems and prospects of state financial control and analysis of local budget execution - Saliamon-Mikhieieva, Kateryna Dmytrivna; Riabchuk, Oksana Hryhorivna; Panasiuk, Olha Viktorivna; Tarashchenko, Volodymyr Anatoliiovych; Bilobrovenko (Moroz), Tetiana Volodymyrivna; Панасюк, Ольга; Оксана, Рябчук; Білобровенко (Мороз), Тетяна (Поліський національний університет, 2022)
In the conditions of the constant increase of global challenges and socio-economic instability, the problem of the effectiveness of state financial control is one of the central ones for modern Ukraine. The purpose of the research was to identify key problems of government financial control and to assess the implementation of local budgets. The main methods for the study of the subject matter were theoretical approaches (analysis of Ukrainian and international theoretical positions), analysis and synthesis, statistical analysis, systematic analysis, terminological analysis, method of graphical representation of statistical data, and analysis of legislative and programme documents. As a result, it was confirmed that necessity to develop the state financial control system and to create a basis for improving the effectiveness of local budget execution had increased. The statistical data for the last three years (in some cases for 10 years) were analysed, which made it possible to describe the current situation in the field of public financial control and execution of local budgets in Ukraine. Shortcomings, problems, obstacles, limitations, and perspectives for public financial control development and the execution of local budgets are identified. The results obtained have theoretical and practical significance. The application of theoretical approaches in the study complements the theoretical provisions financial control of government. The results are of practical importance, especially in the implementation of national policy in the field of state financial control in the context of the crisis caused by the pandemic and its socio-economic consequences.

В умовах постійного наростання глобальних викликів та соціально-економічної нестабільності проблема ефективності державного фінансового контролю є однією з центральних для сучасної України. Мета статті полягала в тому, щоб виявити основні проблеми державного фінансового контролю та провести оцінку виконання місцевих бюджетів. Основні методи до дослідження заявленої у статті проблеми: теоретичні підходи (аналіз українських та міжнародних теоретичних положень), аналіз і синтез, статистичний аналіз, систематичний аналіз, термінологічний аналіз, метод графічного представлення статистичних даних, аналіз законодавчих і програмних документів. У результаті проведеного дослідження підтвердилася висунута автором гіпотеза про значно зростаючу необхідність удосконалення, посилення системи державного фінансового контролю та створення передумов для підвищення ефективності виконання місцевих бюджетів. Виявлено недоліки, проблеми, перешкоди, обмеження та перспективи розвитку державного фінансового контролю та виконання місцевих бюджетів. Отримані результати мають теоретичну та практичну значущість. Застосування теоретичних підходів при дослідженні доповнює теоретичні положення державного фінансового контролю. Практичну значущість мають результати особливо при проведенні національної політики у сфері державного фінансового контролю в умовах кризи, спричиненої пандемією та її соціально-економічних наслідків. За результатами дослідження сформульовано пропозиції щодо вдосконалення системи державного фінансового контролю та виконання місцевих бюджетів.
Keywords: mechanisms of state financial control; national financial system; local budget; financial security of the state; analysis of performance indicators; механізми державного фінансового контролю; національна фінансова система; місцевий бюджет; фінансова безпека держави; аналіз показників ефективності